1992
DOI: 10.1093/oxfordjournals.ndt.a092076
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure after the use of angiotensin-converting-enzyme inhibitors in patients without renal artery stenosis

Abstract: During a 4-year period, acute renal failure was observed in 27 patients (mean age 65 years) treated by various angiotensin-converting-enzyme (ACE) inhibitors for hypertension, heart failure, or a combination of both. None had significant renal artery stenosis on angiography. Overt volume depletion was present in 21 and hypotension in 12 cases. All patients received diuretic therapy and/or a low-salt diet. Other facilitating factors included cardiac failure, pre-existing chronic renal insufficiency, combined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 0 publications
1
28
0
3
Order By: Relevance
“…We have estimated the incidence of development of ARF in NYHA class III and IV CHF patients treated with ACEI in 25%, in accordance with other recent studies [2,3,4,5,6]. The predictors of development of ARF among decompensated CHF patients treated with ACEI, already described are: advanced age, a diagnosis of NYHA class IV CHF, low ejection fraction of left ventricle, concurrent renal insufficiency, and ABP <65 mm Hg.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…We have estimated the incidence of development of ARF in NYHA class III and IV CHF patients treated with ACEI in 25%, in accordance with other recent studies [2,3,4,5,6]. The predictors of development of ARF among decompensated CHF patients treated with ACEI, already described are: advanced age, a diagnosis of NYHA class IV CHF, low ejection fraction of left ventricle, concurrent renal insufficiency, and ABP <65 mm Hg.…”
Section: Discussionsupporting
confidence: 78%
“…The ‘CONSENSUS’ (Cooperative North Scandinavian Enalapril Survival Study) [1] recommends close monitoring of serum creatinine and potassium levels after introduction of ACEI therapy and after an increase in its dosage. This study shows a 20–30% reduction of glomerular filtration rate (GFR) after introduction of enalapril that trends toward stabilization following a 20- to 30-day period; however, other studies have demonstrated a higher reduction in GFR after introduction of ACEI, especially in certain risk groups of patients [2,3,4,5,6]. …”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Some drugs such as clonidine [30,] di-hydropyridines [31,32] and hydralazine [33] hinder renal autoregulation. Ang II antagonists may complicate nephrosclerosis with acute kidney insufficiency in the absence of atherosclerotic renal disease [34] and it is conceivable that overcorrection of hypertension with this class of drugs that act on the glomerular efferent arteriole might in the long-term trade off glomerulomegaly and FSGS for ischemic glomerular obsolescence [35]. …”
Section: Antihypertensive Therapy May Aggravate the Progression To Glmentioning
confidence: 99%